"It's Not About Laziness, It's About Efficiency": Youth Perspectives on Generative AI in Higher Education Through the Lens of TikTok - Literat, Ioana; De Saint Laurent, Constance; Glăveanu, Vlad; Jaffer, Rhea; Kim, Sonia; Diplacido, Sophia (AoIR Selected Papers of Internet Research, 2026)
This study explores how youth discuss generative artificial intelligence (AI) in higher education contexts on TikTok. Through a qualitative analysis of 980 TikTok posts and their associated comments, we identify three key themes: (1) the commercialization of AI tools on TikTok through peer-to-peer marketing strategies, (2) platform-mediated moral contestations around AI ethics and the purpose of higher education, and (3) the emergence of new forms of community-building and identity exploration centered around AI. Our analysis reveals TikTok's significant role as a platform for peer-to-peer knowledge sharing around emerging technologies—yet one deeply marked by commercial dynamics and undisclosed promotional content. These findings contribute to emerging scholarship on how social media platforms shape youth technological imaginaries and provide insights into the complex entanglements of commercial interests, educational discourse, and identity practices in digital spaces.